2018
DOI: 10.1186/s12987-018-0116-3
|View full text |Cite
|
Sign up to set email alerts
|

Erythrophages do not develop when lumbar CSF and blood samples are mixed in vitro

Abstract: BackgroundCerebrospinal fluid (CSF) analysis is a crucial method in the diagnostic process for suspected subarachnoid hemorrhage (SAH), especially when cerebral imaging is negative or inconclusive. CSF cytology (detection of erythrophages or siderophages) is used to determine whether a bloodstained CSF resembles a genuine SAH. Whether erythrophages may develop in vitro after a traumatic puncture in case of delayed CSF analysis is unclear. An in vitro development of erythrophages after traumatic puncture would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
2
3
0
Order By: Relevance
“…Furthermore, it has been supposed that in some cases erythrophages might develop in vitro in the CSF in the presence of artificial blood contamination being not specific for a subarachnoid bleeding (12). Here we have shown that erythrophages and siderophages do not develop in vitro after blood contamination and an incubation time of 24 and 72 h. Our results are in line with the results of Dersch and colleagues who have recently reported that erythrophages do not develop in vitro after 7 h of incubation (13). The presence of xanthochromia in CSF is considered to be another indicator for subarachnoid bleeding in patients with negative CT scan (10, 2830).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, it has been supposed that in some cases erythrophages might develop in vitro in the CSF in the presence of artificial blood contamination being not specific for a subarachnoid bleeding (12). Here we have shown that erythrophages and siderophages do not develop in vitro after blood contamination and an incubation time of 24 and 72 h. Our results are in line with the results of Dersch and colleagues who have recently reported that erythrophages do not develop in vitro after 7 h of incubation (13). The presence of xanthochromia in CSF is considered to be another indicator for subarachnoid bleeding in patients with negative CT scan (10, 2830).…”
Section: Discussionsupporting
confidence: 93%
“…It has been suggested that in some cases erythrophages and siderophages might develop in vitro in the CSF in the presence of artificial blood contamination and thus are not specific for subarachnoid bleeding (12). However, a recent study investigated a short-time (7 h) of incubation of CSF with blood but could not find any evidence of erythrophage development in vitro (13).…”
Section: Introductionmentioning
confidence: 99%
“…Especially for the analysis of subarachnoid hemorrhage, the source of blood is important to know: is it an intrathecal hemorrhage or peripheral blood contamination due to traumatic lumbar puncture? The detection of erythrophages or siderophages does not allow a definitive differentiation in this context [3,36]. In line with our results, Schwenkenbecher et al recently showed that a low amount of blood contamination influences the CSF total protein and CSF/serum albumin quotient, leading to false pathological results.…”
Section: Discussionsupporting
confidence: 61%
“…They are a sign of in vivo rather than in vitro hemorrhage, likely formed and activated by the injury to the choroid plexus and ependymal lining. [ 7 ] There could also be differences in the temperature and incubation time in in vivo versus in vitro settings, which cause them to form only in in vivo . [ 7 8 ] These erythrophages, after 36 to 48 hours, form hemosiderin deposits and are called siderophages.…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] There could also be differences in the temperature and incubation time in in vivo versus in vitro settings, which cause them to form only in in vivo . [ 7 8 ] These erythrophages, after 36 to 48 hours, form hemosiderin deposits and are called siderophages. They persist months after the bleeding.…”
Section: Discussionmentioning
confidence: 99%